Outcomes of Wilms tumor therapy in Lilongwe, Malawi, 2016–2021: Successes and ongoing research priorities. Issue 5 (16th February 2023) - Holmes, David M.; Matatiyo, Apatsa; Mpasa, Atupele; Huibers, Minke H. W.; Manda, Geoffrey; Tomoka, Tamiwe; Mulenga, Maurice; Namazzi, Ruth; Mehta, Parth; Zobeck, Mark; Mzikamanda, Rizine; Chintagumpala, Murali; et al.
Abstract: Introduction: Wilms tumor therapy in low‐ and middle‐income countries (LMICs) relies on treatment protocols adapted to resource limitations, but these protocols have rarely been evaluated in real‐world settings. Such evaluations are necessary to identify high‐impact research priorities for clinical and implementation trials in LMICs. The purpose of this study was to identify highest priority targets for future clinical and implementation trials in sub‐Saharan Africa by assessing outcomes of a resource‐adapted treatment protocol in Malawi. Methods: We conducted a retrospective cohort study of children treated for Wilms tumor with an adapted SIOP‐backbone protocol in Lilongwe, Malawi between 2016 and 2021. Survival analysis assessed variables associated with poor outcome with high potential for future research and intervention. Results: We identified 136 patients, most commonly with stage III ( n  = 35; 25.7%) or IV disease ( n  = 35; 25.7%). Two‐year event‐free survival (EFS) was 54% for stage I/II, 51% for stage III, and 13% for stage IV. A single patient with stage V disease survived to 1 year. Treatment abandonment occurred in 36 (26.5%) patients. Radiotherapy was indicated for 55 (40.4%), among whom three received it. Of these 55 patients, 2‐year EFS was 31%. Of 14 patients with persistent metastatic pulmonary disease at the time of nephrectomy, none survived to 2 years. Notable variables independently associated with survival were severe acute malnutrition (hazard ratio [HR]: 1.9), increasing tumor stage (HR: 1.5), and vena cava involvement (HR: 3.1). Conclusion: High‐impact targets for clinical and implementation trials in low‐resource settings include treatment abandonment, late presentation, and approaches optimized for healthcare systems with persistently unavailable radiotherapy.